Pengaruh Penggunaan Metode Pembelajaran Audio-Visual terhadap Minat dan Hasil Belajar Siswa Mata Pelajaran Ekonomi Kelas 11: (Studi Kasus di SMAN 1 Sutojayan Kabupaten Blitar) - Siti Faridatul Khumairoh; Jani Jani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the influence of using an audio-visual learning method based on animated videos on students' interest and learning outcomes in the subject of Economics for 11th-grade students. The research method used is experimental quantitative. The population of this study consists of 11th-grade students at SMAN 1 Sutojayan, with a purposive sampling technique. The research instruments included a questionnaire to measure learning interest and a cognitive achievement test in the form of multiple-choice questions. The data obtained were analyzed using the t-test with SPSS 27.0 for Windows. The objectives of this study are: 1) To determine whether the use of audio-visual learning methods affects students’ learning interest in Economics at SMAN 1 Sutojayan, Blitar Regency, and 2) To determine whether the use of audio-visual learning methods affects students’ learning outcomes in the same subject and class. The data collection method for learning interest used a questionnaire, while learning outcomes were measured using a post-test. The sample consisted of 62 students from a total population of 340 11th-grade students at SMAN 1 Sutojayan. Data processing included validity testing, reliability testing, prerequisite tests (normality and homogeneity), and hypothesis testing (t-test), all conducted using SPSS 27.0 for Windows. The research results showed: 1) The use of audio-visual learning methods significantly influences students’ learning interest, as evidenced by the sig. (2-tailed) value of 0.000 < 0.05. 2) The use of audio-visual learning methods significantly influences students’ learning outcomes, also evidenced by a sig. (2-tailed) value of 0.000 < 0.05. Furthermore, the average learning interest score in the experimental class (77.29) was higher than in the control class (64.90), and the average learning outcome score was also higher in the experimental class (80.71) compared to the control class (72.58). Therefore, based on these results, H0 is rejected and H1 is accepted.